Wikipédia à tous les étages. Usages de l’encyclopédie pour l’enseignement en géographie - Hadrien Commenges (EchoGéo, 2021)
Wikipedia has always been a research object in several disciplinary fields: computer science, linguistics, geography, political science... Taking Wikipedia as a research object has never been a problem, but using Wikipedia for teaching, especially for university teaching, has always been a problem. A majority of teachers have a suspicious look at the encyclopedia and explicitly recommend students not to use it. Despite these recommendations, students massively use Wikipedia for information retrieval, while considering, after their teachers, that it is an illegitimate source of information. Thus, the encyclopedia has an ambivalent status, it is both used and despised by students and teachers while very few of them are contributors. Wikipedia remains an outsider for university teaching, even though it has many advantages. In this text I propose a feedback from three classes given in the Geography Department of the University of Paris 1 - Panthéon Sorbonne. Based on these experiences, I highlight the interests of using Wikipedia for geography teaching.